2014
DOI: 10.1007/s13197-014-1584-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxinotyping and antimicrobial susceptibility of enterotoxigenic Clostridium perfringens isolates from mutton, beef and chicken meat

Abstract: A total of 300 meat samples comprising mutton, beef, and chicken meat (n=100) collected from either local butcher shops or large meat outlets situated at various areas of Lahore City located in Punjab province of Pakistan were tested for the isolation of Clostridium perfringens. Prevalence of the organism was highest in the chicken (6 %) followed by mutton (5 %) and beef (1 %). Contamination level was high (10/150) in the samples collected from local butcher shops in comparison to the samples collected from la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…In another study, penicillin was found 100% sensitive against clostridia species (Novak et al, 2015). In Pakistan, Khan et al (2014) studied the susceptibility of C. perfringens against antibiotics and results resembled the current study as they declared penicillin, ciprofloxacin and ceftriaxone as sensitive antibiotics while amoxicillin as resistant. Recently, Yadav et al (2017) studied different antibiotics sensitivities against C. perfringens and found 83.7% isolates resistant against three or more antibiotics.…”
Section: Discussionsupporting
confidence: 69%
“…In another study, penicillin was found 100% sensitive against clostridia species (Novak et al, 2015). In Pakistan, Khan et al (2014) studied the susceptibility of C. perfringens against antibiotics and results resembled the current study as they declared penicillin, ciprofloxacin and ceftriaxone as sensitive antibiotics while amoxicillin as resistant. Recently, Yadav et al (2017) studied different antibiotics sensitivities against C. perfringens and found 83.7% isolates resistant against three or more antibiotics.…”
Section: Discussionsupporting
confidence: 69%
“…Table 3 shows that out of 32 C. perfringens strains, six of enterotoxigenic strains belonged to type A, two to type D, and one to type E. This is similar to observations of Khan et al . ( 16 ) who toxinotyped six C. perfringens isolates from raw chicken meat and found that three of them were of type A and one each of the remaining three belonged to types B, C, and D. Likewise, the recognition of enterotoxin genes in type A isolates collected from raw and processed chicken meat products was reported by Guran and Oksuztepe ( 13 ). Moreover, the prevalence of C. perfringens exotoxin and enterotoxin was not related to the type of product (P > 0.05) ( Tables 2 and 3 ).…”
Section: Discussionmentioning
confidence: 86%
“…Studies conducted on C. perfringens prevalence in raw poultry meat products at retail in the United States, in Japan, in India and in Canada revealed that between 6% and 97% of the analyzed meat samples were positive for the presence of C. perfringens . However, the presence of cpe or cpe -carrying C. perfringens strains among those meat samples was varying between 0% and 15.5% [7][10],[12],[36],[37]. To our knowledge, no cross-sectional study has yet been done to investigate the prevalence of cpe -positive broiler chicken flocks and carcasses at the slaughter plant level, nor the critical steps of the slaughter process involved in this contamination have been identified [23],[38].…”
Section: Discussionmentioning
confidence: 99%